การนำชื่อโดเมนมาเป็นหลักประกันการชำระหนี้ - สมพร เหลี่ยมป้อ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
Domain name is a kind of intellectual property which exclusive rights are granted to its legitimate owner to use such domain name and prevent others from using it. It is also considered as a property right pursuant to Section 138 of the Civil and Commercial Code, as well as an economic right which can be appraised in monetary value and transferred from one holder to another.Domain name is an incorporeal object which can be recorded under the Accounting Standard No. 51 (2007 revision) as an "Intangible Asset". There are three methods for valuation of domain names, i.e. (1) The Cost Approach, (2) The Comparison/Market Approach and(3) The Income Approach. The researcher investigated and compared three alternatives for using domain name as collateral. The first option is to provide a contract with a precedent condition or a subsequent condition according to Section 183 of the Civil and Commercial Code. The second option is to amend Section 703 paragraph two of the Civil and Commercial Code to allow a domain name to be mortgaged. The third option is to include domain name as a collateral under Section 8(5) of the Secured Transaction Bill, by issuing the Ministerial Regulation stipulating domain name as a type of property which can be used as collateral. Among those alternatives, the researcher is of the view that use of domain name as collateral under the aforesaid Bill is the best choice because the grantor is capable of using his domain name during the term of collateral agreement while the grantee’s right is also recognized in the position of secured creditor. Regarding the procedure for executing domain name as collateral, it can be conducted in two ways. The first one is to put domain name on auction sale through websites. The second one is to claim foreclosure of domain name so that the grantee can further exploit domain name for his own business.